Estudo comparativo do uso da terapia fotodinâmica antimicrobiana (aPDT) com uso sistêmico de amoxicilina e metronidazol, no tratamento da periodontite crônica em pacientes fumantes - Assem, Naida Zanini [UNESP] (2015)
Aim: The aim of this study was to evaluate the clinical and microbiological effects of Metronidazolecombined with Amoxicillin (MTZ+AMX) and multiple applications of antimicrobial photodynamic therapy (aPDT) as adjuvant treatment of smokers with chronic periodontitis. Methods:A double-blind controlled, randomized clinical trial was conducted in 51 smoking patients who received: SRP Group (n=17): scaling and root planning and placebo; MTZ+AMX Group (n=17) and SRP with systemic use of Metronidazole (400 mg 3 X per day 7 days) and Amoxicillin (500 mg 3 X per day 7 days); aPDT Group (n=17): SRP and three aPDT applications at two sites (one moderate and one deep pocket) per quadrant, immediately 48 and 72 hours after scaling and MTZ and AMX (placebo) during 7 days. Clinical and microbiologic examinations were performed at Baseline, 3 and 6 months post-therapy. Clinical parameters of visible plaque index (VPI), bleeding on probing (BOP), probing depth (PD), and clinical attachment level (CAL) were measured. Samples were collected from a subgingival pocket ≥ 4mm ≤ 6mm (pocket moderate) and another ≥ 7mm (pocket deep) in each quadrant of each patient, in the groups SRP, MTZ+AMX and aPDT. The APDT was carried out using methylene blue and the laser low level after 1 minute (GaAlAs 660 nm, 100 mW, 48 seconds, 160 J/cm²) 48 and 72 hours immediately after treatment, into the same sites of the collection. For microbiological analysis, three periodontal pathogens were assessed by polymerase chain reaction in real time (PCR-real time): Porphyromonas gingivalis (Pg), Prevotella nigrescens (Pn) e Prevotella intermedia (Pi).The statistical analysis was performed (α=5%). Results: Treatments with MTZ + AMX and aPDT promoted improvements in PD, CAL, BOP and VPI parameters after treatment. Patients who received the treatment with aPDT showed a higher reduction of CAL and PD in pockets collected, when...